Gestión de inventarios en el comisariato promociones 2000 de la parroquia la Unión - Badillo Almeida, Katherine Solange (2022)
Inventory management is a fundamental part of any company, it is what allows it to function properly, because talking about inventory is not only knowing if a company is liquid or not according to the audit carried out at the end of the year. ; It is not only knowing how much income in profits and how much was invested in each of the products, this goes further because it refers to and is also part of the administrative processes that are carried out in a commercial place, since knowing how to plan, direct, control and execute, has its cause and effect that directly reflects the company. Within an inventory there are several types of management that can be applied, this goes hand in hand with the supply and all the processes that they entail, since the quality of the final product that is offered to the consumer depends on this, together with the indicators of management that it is of the utmost importance to apply them so that there is no chaos or storage disorder. Provisioning is part of the commercial premises as well as of the suppliers, because it is useful to know when to order and how much to order according to the size available in stock, avoiding excess and shortage of stock so that the establishment does not have losses.